Malefícios provenientes da contrafação de drogas sintéticas e sua relação com a era informatizada - Gonçalves, Gustavo Leite (Universidade Federal Rural do Semi-Árido, 2016)
Synthetic drugs are psychotropic drugs formulated in the laboratory, considered clean drugs, they do not require special preparation for use. They possess unwieldy by ANVISA, the supervisory body of drug abuse because of the speed with which they are created or modified. The consumption of hallucinogens has been increasing and expanding recently, particularly among young people, attending parties and electronic environments where they can be found more easily. Taking advantage of this fact, many dealers try to increase their sales worrying less and less with the lives of users by manipulating the products of uncontrolled way, with unimaginable ingredients, such as drugs for hypertension, which can cause irreversible damage or even death. The purchase and sale of these products is following the advancement of technology, decentralizing the slums and leaving for the virtual era. Smugglers sell their items by Deep Web, an almost lawless environment, little known by the police, causing the illicit reach the home users for own mail, barring further investigations.
Keywords: Drogas de abuso; Deep web; Adulteração; Abused drugs; Deep web; Tampering; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA